1988
DOI: 10.1071/ea9880077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depth of burial on the longevity of hard seeds of subterranean clover and annual medics

Abstract: Burrs of 3 cultivars of subterranean clover (Trifolium subterraneum) and 1 cultivar each of burr medic (Medicago polymorpha) and barrel medic (M. truncatula), which had experienced 1 summer at the soil surface, were placed on the soil surface and at depths of 2, 6 and 10 cm in the soil. The numbers of residual hard seeds were determined each year for up to 4 years. There was a marked reduction in the rate of seed softening in all 3 clover cultivars with increasing depth of burial. Whereas <20% of the seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…Previous environmental conditions imposed on the soil over many years in the field may have reduced the effects of laboratory imposed wet-dry cycles on the mineralization of organic C. During summer the surface temperature of soils in southern Western Australia can reach 60°C (Taylor and Ewing, 1988) and rainfall is frequently intermittent at the start and end of the winter growing season (Cornish, 1985) resulting in numerous wet-dry cycles. Drying of a sand soil at 85 °C greatly increased the subsequent mineralization of organic C compared to that in continuously moist soil (Jager and Bruins, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Previous environmental conditions imposed on the soil over many years in the field may have reduced the effects of laboratory imposed wet-dry cycles on the mineralization of organic C. During summer the surface temperature of soils in southern Western Australia can reach 60°C (Taylor and Ewing, 1988) and rainfall is frequently intermittent at the start and end of the winter growing season (Cornish, 1985) resulting in numerous wet-dry cycles. Drying of a sand soil at 85 °C greatly increased the subsequent mineralization of organic C compared to that in continuously moist soil (Jager and Bruins, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…In annual medics (Medicago spp.) and T. subterraneum, the seed dormancy release rate decreased as burial depth increased (Taylor and Ewing 1988), and Biserrula pelecirtzts occurred more rapidly at 2 cm depth than that at 6 cm (Revell et al 1998). In contrast with that, the dormancy release rate of Ornithopus compressus seed was more rapid when buried 2 cm below the soil surface than that left on the soil surface (Loi et al 1999).…”
Section: Introductionmentioning
confidence: 93%
“…The most common situation is seed that was buried at different soil depths as consequences of various management or natural processes, e.g., grazing, tillage, sand moving, etc. Previous researches (Taylor and Ewing 1988;Loi et al 1999) have shown that burial depth could affect physical dormancy release. In annual medics (Medicago spp.)…”
Section: Introductionmentioning
confidence: 97%
“…Buried seeds of some legume species can survive as hard seeds for up to 12 years without significant loss of viability (Taylor and Ewing, 1988), which increases the seed longevity and population persistence. High hardseedness contributes to persistent soil seed bank by preventing germination from season rainfall and allows a certain proportion of a seed population to survive even in extended drought (Norman et al, 1998).…”
Section: Discussionmentioning
confidence: 99%